Contributions of research to the advances in moral education (2022)
Objective: This article presents a review of research perspectives that have become referents for the moral formation of citizens. Originality/contribution: the debate is enriched through a different reflection. It analyzes the advances in moral education based on the different research approaches whose development, in this field, began in the early 20th century. Some of them are as follows: personal internalization of behavior, the adaptation of individuals to social norms, autonomous construction of moral reasoning, and social learning as a source of moral education. Method: The study is based on the analysis of the existing literature, alternating between research advances in the moral field and the epistemological development of the concepts of this dimension. Strategies/information collection: The process consists of three stages: identification of research that has contributed to the theory of moral education, categorization by lines of research based on the similarity between approaches, and analysis of each approach. Conclusions: Four research approaches in moral education are identified: internalization of behavior, adaptation of the person to social norms, autonomous construction, and social learning. The first two with a focus on the heteronomous assumption of behavioral patterns, and the other two on the autonomy of individuals in interaction with the social context.